Participation of lipopolysaccharide in hyperplasic adipose expansion: Involvement of NADPH oxidase/ROS/p42/p44 MAPK‐dependent Cyclooxygenase‐2. Issue 14 (1st June 2022) - Chang, Chao‐Chien; Sia, Kee‐Chin; Chang, Jia‐Feng; Lin, Chia‐Mo; Yang, Chuen‐Mao; Lee, I‐Ta; Vo, Thi Thuy Tien; Huang, Kuo‐Yang; Lin, Wei‐Ning
Abstract: Obesity is a world‐wide problem, especially the child obesity, with the complication of various metabolic diseases. Child obesity can be developed as early as the age between 2 and 6. The expansion of fat mass in child age includes both hyperplasia and hypertrophy of adipose tissue, suggesting the importance of proliferation and adipogenesis of preadipocytes. The changed composition of gut microbiota is associated with obesity, revealing the roles of lipopolysaccharide (LPS) on manipulating adipose tissue development. Studies suggest that LPS enters the circulation and acts as a pro‐inflammatory regulator to facilitate pathologies. Nevertheless, the underlying mechanisms behind LPS‐modulated obesity are yet clearly elucidated. This study showed that LPS enhanced the expression of cyclooxygenase‐2 (COX‐2), an inflammatory regulator of obesity, in preadipocytes. Pretreating preadipocytes with the scavenger of reactive oxygen species (ROS) or the inhibitors of NADPH oxidase or p42/p44 MAPK markedly decreased LPS‐stimulated gene expression of COX‐2 together with the phosphorylation of p47 phox and p42/p44 MAPK, separately. LPS activated p42/p44 MAPK via NADPH oxidase‐dependent ROS accumulation in preadipocytes. Reduction of intracellular ROS or attenuation of p42/p44 MAPK activation both reduced LPS‐mediated COX‐2 expression and preadipocyte proliferation. Moreover, LPS‐induced preadipocyte proliferation and adipogenesis were abolished by the inhibition of COX‐2 or PEG2 receptors. Taken together, our results suggested that LPS enhanced the proliferation and adipogenesis of preadipocytes via NADPH oxidase/ROS/p42/p44 MAPK‐dependent COX‐2 expression.